2015
DOI: 10.1016/j.eurpolymj.2015.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation of alkyl sulfonate initiators for the cationic ring-opening polymerization of 2-oxazolines revealing optimal combinations of monomers and initiators

Abstract: A systematic kinetic investigation of the living cationic ring-opening polymerization (CROP) involving 2-ethyl-2-oxazoline, 2-methyl-2-oxazoline, and 2-phenyl-2-oxazoline employing a series of alkyl sulfonate initiators with variation of the alkyl initiating fragment (methyl, ethyl, iso-propyl) and the leaving group/counterion (tosylate, nosylate, triflate) is reported. The study reveals that the initiation and propagation reactivity increases in the order tosylate < nosylate < triflate. Slow initiation is ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 30 publications
3
63
1
1
Order By: Relevance
“…Similar result (k p = (1.59 ± 1.7) Â 10 À3 L mol À1 s À1 ) was obtained for the polymerization of the 2-nonyl-2-oxazoline initiated by iodomethane in dimethylacetamide, a solvent of close dielectric constant to acetonitrile, at the same temperature [38]. It should be noticed that the kinetic studies for the polymerization of 2-methyl-2-oxazoline initiated with iodoalkane revealed lower k p values than the ones reported recently with a range of sulfonate initiators (k p = (6.02 ± 0.31) Â 10 À3 L mol À1 s À1 in the case of ethyl nosylate) [39]. The number-average molecular weight was plotted against conversion for both monomers with an expected molecular weight of 8 Â 10 À3 g mol À1 (Fig.…”
Section: Synthesis Of Homopolymersmentioning
confidence: 59%
“…Similar result (k p = (1.59 ± 1.7) Â 10 À3 L mol À1 s À1 ) was obtained for the polymerization of the 2-nonyl-2-oxazoline initiated by iodomethane in dimethylacetamide, a solvent of close dielectric constant to acetonitrile, at the same temperature [38]. It should be noticed that the kinetic studies for the polymerization of 2-methyl-2-oxazoline initiated with iodoalkane revealed lower k p values than the ones reported recently with a range of sulfonate initiators (k p = (6.02 ± 0.31) Â 10 À3 L mol À1 s À1 in the case of ethyl nosylate) [39]. The number-average molecular weight was plotted against conversion for both monomers with an expected molecular weight of 8 Â 10 À3 g mol À1 (Fig.…”
Section: Synthesis Of Homopolymersmentioning
confidence: 59%
“…MeONs was proved to be a suitable initiator for living cationic polymerization of 2-oxazolines, with the propagation rate coefficient slightly lower as that of methyl triflate. 29 In comparison to methyl triflate, MeONs exhibits an increased stability during storage and easier synthesis and purification.…”
Section: Resultsmentioning
confidence: 99%
“…In the first step a nucleophilic attack of the nitrogen lone pair of the 2‐oxazoline monomer onto an electrophilic initiator forms an oxazolinium cation, initiating the polymerization reaction. Different initiator systems can be used including alkyl sulfonates such as methyl p ‐toluenesulfonate, which is most frequently mentioned in the literature, p ‐nitrobenzenesulfonates (nosylates) and trifluoromethanesulfonates (triflates), alkyl, benzyl and acetyl halides, oxazolinium salts and Lewis acids . Also functional initiators can be used as long as they do not bear any nucleophilic character that could interfere with the CROP.…”
Section: Cationic Ring‐opening Polymerization Of 2‐oxazolinesmentioning
confidence: 99%